The Mexican Mafia - Rafael, Tony (Encounter Books, 2007)
It has been called the most dangerous gang in American history. In Los Angeles alone it is responsible for over 100 homicides per year. Although it has fewer than 300 members, it controls a 40,000-strong street army that is eager to advance its agenda. It waves the flag of the Black Hand and its business is murder. Although known on the streets for over fifty years, the Mexican Mafia has flown under the radar of public awareness and has flourished beneath a deep cover of secrecy. Members are forbidden even to acknowledge its existence. For the first time in its history, the Mexican Mafia is no.